(In)visibilidade de jovens e adultos negros na educação profissional e EJA: desafios para implementação da educação sobre as relações étnico-raciais - Prates, Ana Maria da Rosa (2025)
The thesis addresses the issue of invisibility of black youth and adults in the National Program for the Integration of Professional Education with Basic Education, in the Youth and Adult Education Modality (PROEJA) and the Youth and Adult Education Program Integrated with Professional Education (EJA - EPT) of the Federal Institute of Education, Science and Technology of Rio Grande do Sul, campus Sertão - RS. In the literature and current criticism, invisibility is identified as one of the forms of exclusion that black youth and adults face in the process of social life and work. The aim is to clarify whether the provision of secondary education in the Youth and Adult Education (EJA) modality of the Technical Course in Commerce and the Technical Course in Administration, at the Federal Institute of Education, Science and Technology of Rio Grande do Sul- IFRS, campus Sertão - RS, complies with the guidelines established by Brazilian legislation on the education of ethnic-racial relations. In particular, the aim is to identify the extent to which this educational provision promotes an anti-racist approach, as advocated in Law 10.639/2003 and the National Curriculum Guidelines for Education on Ethnic-Racial Relations. The research proposal involves analyzing the formal conformity of the curricula and educational practices proposed by PROEJA and EJA Integrada - EPT, comparing the legal guidelines with the organization and curricular structure in force in the courses, especially concerning the inclusion and appreciation of black young people and adults. The study aims to specifically examine the possible processes of exclusion and invisibilization that persist in the respective courses. The relevance of the study is evidenced by the persistent racial inequality in the Brazilian educational system, as demonstrated by research such as that of Gomes (2005), Munanga (2000, 2004, 2005), Silva (2004, 2005), Wieviorka (2007), Almeida (2019), Carneiro (2005), Cavalleiro (2001), Tavares (2010), and Santos (2011), that point out the reproduction of stereotypes and the predominant superficiality in the treatment of Afro-Brazilian history and culture in schools. We start from the hypothesis that, despite the growing recognition of the importance of racial issues and the implementation of this law and its guidelines, its implementation in everyday practices in the projects of the IFRS - campus Sertão - RS still faces significant challenges. Among the factors that interfere, we highlight the lack of adequate training for educators, resistance to curricular changes and insufficient resources for the effective implementation of the guidelines. The results reveal that developing EJA from an anti-racist education perspective requires creating effective democratic forms of training in all instances of school education. Achieving these objectives requires consistency with the principles adopted in ethnic-racial education.